A case of multilevel percutaneous vertebroplasty for vertebral metastases resulting in temporary paraparesis. Issue 2 (October 2020) - Shi, Guan; Feng, Fei; Hao, Chen; Pu, Jia; Li, Bao; Tang, Hai
Percutaneous vertebroplasty (PVP) is a minimally invasive treatment that has been widely used for the treatment of osteoporotic vertebral compression fractures and vertebral tumors. However, the maximum number of vertebral segments treated in a single PVP remains controversial. Furthermore, PVP may cause complications, including cement leakage, pulmonary embolism, bone cement toxicity, and spinal nerve-puncture injury. We report the rare case of a patient who underwent multilevel PVP for vertebral metastases, with no bone cement leakage or spinal cord injury, but who developed temporary paraparesis.